2020
DOI: 10.1016/j.ejim.2020.05.031
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of cancer-associated thromboembolic disease in 2018–2019: First data from the TESEO prospective registry

Abstract: Background: The ever-growing complexity of cancer-associated thrombosis (CAT), with new antineoplastic drugs and anticoagulants, distinctive characteristics, and decisions with low levels of evidence, justifies this registry. Method: TESEO is a prospective registry promoted by the Spanish Society of Medical Oncology to which 34 centers contribute cases. It seeks to provide an epidemiological description of CAT in Spain. Results: Participants (N=939) with CAT diagnosed between July 2018 and December 2019 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…The distribution of the sites of cancer was also similar to that seen in the population of patients with cancerassociated VTE as shown by the most recent prospective study on cancer and VTE. 22 Strengths of this analysis include the large sample of patients enrolled in the study and the characteristics of the study population with the inclusion of a large proportion of patients with advanced cancer who represent the most challenging patients.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the sites of cancer was also similar to that seen in the population of patients with cancerassociated VTE as shown by the most recent prospective study on cancer and VTE. 22 Strengths of this analysis include the large sample of patients enrolled in the study and the characteristics of the study population with the inclusion of a large proportion of patients with advanced cancer who represent the most challenging patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the thromboembolic events were seen to be early, although slightly dissimilar patterns are apparent in different sites of primary cancer, as already seen in the most recent prospective study. 20 This observation indicates the need to evaluate longitudinally the thrombotic risk and the occurrence of VTE, taking into account the differences in the course of the disease that can have a homogenous evolution, as pancreatic cancer, or alternate remissions and relapses, as ovarian or breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The p-value of each regression is presented, as well as 2 the odd ratios that express the relation between the expression of each gene and thrombotic risk in the full cohort. Similarly, 3 the confidence interval (95%) of each odd ratio is shown. 4 The odd ratios above 1 on this axis indicated that the greater the gene expression, the greater associated thrombotic risk in the overall cohort, whereas values of less than 1 indicated that the greater the expression, the lower the associated risk.…”
Section: Conditional Logistic Regression By Histopathology In the Ove...mentioning
confidence: 99%